Penguatan Nilai Karakter Perang Badar untuk Dunia Pendidikan - Muhammad Hariyadi; Moh Kholis Fathulloh (LP2M Universitas PTIQ Jakarta, 2017)
The war of Badar is one of the very special warfare for the Muslims. In addition to being the first war that had a positive effect on the development of the Muslims in Medina, the war broke up convincing Muslims that their religion was the most correct religion on earth. This article deals with some of the characters that writers can analyze from the war of Badar, including: Fully obeying God and His Messenger, the habit of endless Zikr, firmly established in fighting for any religion as a consequence, avoiding disputes among muslims, patience in all circumstances, and call trusting God after completing various activities that are the cause of everything. These six characters are implemented in the Education world through exemplary methods, habituation methods, story methods and extracurricular activities that have a very significant influence and influence in cultivating discipline, enthusiasm, toughness, patience and the strength of the soul in the taught personal lessons.